Building Energy Impacts of Simple Green Roofs in the Hot Summer and Cold Winter Climate Zone: Suzhou as a Study Case. (2017) - Tian, Zhen; Lei, Yaping; Gu, Xin
Abstract: This paper explores the building energy impacts of simple green roofs in the hot summer and cold winter climate zone, using Suzhou as the study case city. The study finds that simple roofs can reduce building peak heating and cooling loads. Simple green roofs can also save building cooling and heating energy uses in the hot-Summer and cold-Winter climate. With the insulation and thermal mass effect of green roof construction, simple green roofs can be equivalent to the insulation effect of public buildings insulation requirements in the Jiangsu Province. The study results also indicate that simple green roofs may replace the insulation required in building energy standard, especially in the design of existing building energy renovation, and the insulation layer with green roof may not be necessary, saving energy cost as well as construction cost.